RESEARCH OF THE DEVELOPMENT OF THE MOTIVATIONAL COMPONENT OF THE COGNITIVE ACTIVITY OF SENIOR PRESCHOOLERS - E. Gribova; T. Poshtareva (Вестник Северо-Кавказского федерального университета, 2022)
The article reveals the essence of cognitive activity, and also provides data from an empirical study of such components of the motivational component of the cognitive activity of older preschoolers as cognitive needs and cognitive interest. The authors, in accordance with the results of primary diagnostics, indicating a rather low level of development of the motivational component of cognitive activity in older preschoolers, puts forward a hypothesis about the need to introduce didactic principles into the educational process that qualitatively improve the development of the cognitive needs and interest of children. Such principles, according to the authors, are the following principles: individualization, consciousness and activity, eventfulness and the creation of cognitive situations, variability, gradual overcoming of difficulties, a favorable emotional climate and positive motivation, creativity.